Evaluation of total phenolic contents and antioxidant capacities of Momordica charantia L. (Bitter gourd) fruits - Ayşe BALDEMİR; Kübra EKİNCİ; Selen İLGÜN; Akife DALDA; Halit YETİŞİR (Derim, 2018)
In this study, raw and mature fruits of 13 different genotypes of Momordica charantia L. (Cucurbitaceae) collected from different regions of Turkey were used. F3 seeds of the genotypes were produced for two years by selfing. Pulp parts of raw and ripe fruits of different genotypes were separated and 70% methanol extracts were prepared by Soxhlet extraction from these parts. Total phenolic contents of the extracts and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities were determined. As a result, genotypes 3, 8 and 9 for M. charantia fruit were found to be particularly promising.